Proceedings of Seminars Meetings Received - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
Food security issues in Southern Africa, Maseru, Lesotho,January 1214,1987, organized by the Institute of Southern African Studies, National University of Lesotho, and spon sored by CTA. ISBN 92 90810319, Available from: CTA - Postbus 380 - 6700...